The European Union : a very short introduction - Pinder, John. (Oxford ; New York : Oxford University Press, 2001)
John Pinder writes with expert knowledge of the European Union but in plain, readable English. He shows how and why the Union has developed from 1950 up to now. He explains the interplay between governments and federal elements in the institutions; consensus over the single market and the environment; conflicts over agriculture, social policies, the euro, frontier controls. He shows how the Union relates to its European neighbours, the United States, and the rest of the world. And he outlines the choices that lie ahead. He is clear about his federalist orientation, presents the arguments fairly, and is scrupulous about the facts. This is quite simply the best short book on the subject.
1 What the EU is for; 2 How the EU was made; 3 How the EU is governed; 4 Single market, single currency; 5 Agriculture, regions, budget; 6 Social policy, environmental policy; 7 'An area of freedom, security and justice'; 8 A great civilian power ... and more, or less?; 9 The EU and the rest of Europe; 10 The EU and the world; 11 So far so good ... but what next?
Includes bibliographical references (pages 168-173) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: European Union; LAW -- International; Law